2020
DOI: 10.1111/apa.15435
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 epidemics in paediatric morbidity and utilisation of Hospital Paediatric Services in Italy

Abstract: we read with great interest the article by Pata et al. published online on June 2 nd in the Journal (1). Indeed, the current Covid‐19 epidemic in Italy and the associated, two months (March‐April) strict lockdown have impacted on the overall epidemiology and use of adult and pediatric medical resources –also due to dramatic changes in lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 1 publication
(1 reference statement)
3
21
0
1
Order By: Relevance
“…Indeed, being our hospital qualified as COVID-19 hospital, our ED was efficiently reorganized to avoid intrahospital spread of SARS-CoV-2, separating suspected COVID-19 and standard care pathways. We detected only 1 case positive to SARS-CoV-2 (a 1.9-year-old girl admitted for complex febrile seizure) among 68 symptomatic and 47 asymptomatic patients tested with nasopharyngeal swab, confirming the low prevalence of COVID-19 among children and adolescents reported by other Italian records [7,8,17,27]. Febrile seizures represent a rare presentation of COVID-19 in pediatric age.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Indeed, being our hospital qualified as COVID-19 hospital, our ED was efficiently reorganized to avoid intrahospital spread of SARS-CoV-2, separating suspected COVID-19 and standard care pathways. We detected only 1 case positive to SARS-CoV-2 (a 1.9-year-old girl admitted for complex febrile seizure) among 68 symptomatic and 47 asymptomatic patients tested with nasopharyngeal swab, confirming the low prevalence of COVID-19 among children and adolescents reported by other Italian records [7,8,17,27]. Febrile seizures represent a rare presentation of COVID-19 in pediatric age.…”
Section: Discussionsupporting
confidence: 81%
“…A significant reduction in pediatric ED consultations (ranging from 73 to 84%) during COVID-19 pandemic has been reported also by few other Italian hospitals of Northern , showing a 76.3% decrease [20], a finding similar to our results. Furthermore, Italian studies reported that pediatric patients had more appropriate accesses to ED during COVID-19 pandemic [16,17,20]. Thus, available data suggest that even if COVID-19 outbreak more seriously affected Northern Italy, utilization of pediatric emergency services significantly changed in the entire country with consequent reduced demand and increased appropriateness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight were from China, 45,50,68,70,72-74,77 7 from other low and middle-income countries (LMIC; Turkey, 58,79 Pakistan, 25 India, 28,65 Brazil, 55 Bangladesh 76 ) and 13 from Italy, 23,26,27,32,35,38,49,56,78,81,84-86 21 from the UK, 22,29-31,37,39-42,44,47,48,54,60,62-64,69,87,89,90 12 from the USA, 24,43,46,51,57,59,66,67,71,75,92,94 and 1 study each from Ireland, 88 France, 91 Germany, 93 Greece, 80 Spain, 61 Finland, 34 Slovenia, 33 Israel, 82,83 Australia, 52 Canada 53 and Japan. 36…”
Section: Resultsmentioning
confidence: 99%
“…A notable drop in pediatric admissions for acute lower respiratory tract infections (LRTI) other than COVID-19, particularly viral LRTI, has been described in a number of countries (26)(27)(28). In the Southern Hemisphere, the COVID-19 pandemic coincided with the annual 2020 viral respiratory season.…”
Section: Covid-19: Impact On Acute Lower Respiratory Tract Infectionsmentioning
confidence: 99%